Governmental use of Twitter A questionnaire study on a sample of Twitter users in Saudi - Al-Rateeq, Hassah Muhammad (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aims to identify the reality of the government’s use of Twitter, including the degree of citizens ’use of government pages, and the reality of citizens’ access to information and participation through their use of government pages on Twitter. Based on the nature of the objectives of this study, the analytical descriptive method was used. The researcher prepared an electronic questionnaire. The number of completed responses reached (334). The study found that the large percentage of the sample (67%) ranged in age from 20 to less than 30 years, and this confirms that the means of social communication is being adopted by a higher proportion of young people. Almost half of the sample (49%) uses a public Internet search engine as a primary option for government information, and this may be due to the ease of finding information through search engines. On the other hand, the study found that nearly half of the sample is not satisfied with the level of information they receive and the level of their participation in the government pages on Twitter, and this may reflect the high expectations of the respondents towards the progress of government pages.The study presented a number of recommendations.